First Results From Sonification and Exploratory Citizen Science of Magnetospheric ULF Waves: Long‐Lasting Decreasing‐Frequency Poloidal Field Line Resonances Following Geomagnetic Storms. Issue 11 (9th November 2018) - Archer, M. O.; Hartinger, M. D.; Redmon, R.; Angelopoulos, V.; Walsh, B. M.; ,
Abstract: Magnetospheric ultralow‐frequency (ULF) waves contribute to space weather in the solar wind‐magnetosphere‐ionosphere system. The monitoring of these waves by space‐ and ground‐based instruments, however, produces big data, which are difficult to navigate, mine, and analyze effectively. We present sonification, the process of converting an oscillatory time series into audible sound, and citizen science, where members of the public contribute to scientific investigations, as a means to potentially help tackle these issues. Magnetometer data in the ULF range at geostationary orbit have been sonified and released to London high schools as part of exploratory projects. While this approach reduces the overall likelihood of useful results from any particular group of citizen scientists compared to typical citizen science projects, it promotes independent learning and problem solving by all participants and can result in a small number of unexpected research outcomes. We present one such example, a case study identified by a group of students of decreasing‐frequency poloidal field line resonances over multiple days found to occur during the recovery phase of a coronal mass ejection‐driven geomagnetic storm. Simultaneous plasma density measurements show that the decreasing frequencies were due to the refilling of the plasmasphere following the storm. The waves were likely generated by internal plasma processes. Further exploration of the audio revealed many similar events following other major storms; thus, they are much more common than previously thought. We therefore highlight the potential of sonification and exploratory citizen science in addressing some of the challenges facing ULF wave research. Plain Language Summary: Earth's magnetic shield, protecting us against harmful radiation from the Sun and more distant sources, is rife with a symphony of ultralow‐frequency analogues to sound waves. These waves transfer energy from outside this shield to regions inside it and therefore play a key role in space weather. While they are too low pitch for us to hear them, we can make our satellite recordings of them audible by dramatically speeding up their playback. We show the audio can be used by school students to contribute to research, by having them explore through the act of listening and performing analysis using audio software. An example of this is presented where London school students identified waves whose pitch decreased over the course of several days. The waves were the natural oscillations of magnetic field lines, like the vibrations of a plucked guitar string, which forms a distinct note. The changing pitch is explained by the fact that the event occurred as Earth's magnetic shield was recovering from a disturbance caused by a solar storm . Many similar events were discovered in the audio, which also followed such disturbances, revealing that these types of waves are much more common than previously thought. Therefore, we have demonstrated that making data audible and involving the public can further the research into space weather. Key Points: Sonification can be used for exploratory citizen science, in this case of ultralow‐frequency waves at geostationary orbit Long‐lasting narrowband poloidal field line resonances with decreasing frequency have been identified Such events occur more often than previously thought, typically in the recovery phase of geomagnetic storms